A problem of sexual dimorphism among plio-pleistocene - Hałaczek, Bernard (Anthropological Review, 1981)
The author reviews literature for all existing information upon sexual dimorphism in morphology of early hominids. He concludes that it is impossible to reconstitute precisely the dimorphism of our ancestors and thus considerations upon diminishing sexual dimorphism in human evolution are pure speculations.